Generalizations of the Suzuki and Kannan Fixed Point Theorems in G-Cone Metric Spaces (Analysis in Theory and Applications, 2012)
In this paper we develop the Banach contraction principle and Kannan fixed point theorem on generalized cone metric spaces. We prove a version of Suzuki and Kannan type generalizations of fixed point theorems in generalized cone metric spaces.
Keywords: fixed point; $D$-metric space; 2-metric space; generalized cone metric space; Kannan mapping; generalized Kannan mapping; contractive mapping.